MORPHOMETRY OF FASCIOLA GIGANTICA THAT INFECTS BALI CATTLE IN BALI - Pratama, Gilang Andri; Suratma, Nyoman Adi; Apsari, Ida Ayu Pasti (Buletin Veteriner Udayana, 2023)
Disease disturbance in livestock is one of the obstacles faced in the development of livestock. One of these diseases is a parasitic disease caused by the liver fluke Fasciola spp . known as Dystomatosis, or Fasciolosis. It is known that F. intermedia was found which was characterized based on its morphology. This F. intermedia worm has been found in Pakistan and Iran, based on the results of the analysis F. gigantica and F. intermedia from Pakistan have close proximity to species that exist in Iran. It is important to study morphometry, especially at the Pesanggaran Slaughterhouse (RPH) to see the possibility of F. intermedia in Indonesia, especially in Bali. This study used samples of F. gigantica worms which consisted of 30 samples of worms from 10 gall bladders of Bali cattle obtained from the Pesanggaran Slaughterhouse (RPH). Then, macroscopic and microscopic observations were made. Macroscopic observations were carried out by measuring the length and width of the worm's body while microscopic observations were carried out by observing under a microscope after staining with the Semichoen Acetic Carmine method. From the results of morphometric measurements of the worm F. gigantica , the lowest and highest sizes of the worms were body length (PB) of 20.9 mm with the highest size of 35 mm with an average body length of 29.47667 mm. While the lowest size of the body width (LB) of the worm is 5.3 mm and the highest size is 8.4 mm with an average body width of 7.166667 mm. Based on the size obtained, the studied F. gigantica can be classified into intermediate species (intermedia). The author suggests that there is a need for sanitation in the cattle rearing system in Bali and the provision of deworming drugs to cows.